Upaya Meningkatkan Motivasi Belajar Siswa Sekolah Menengah Pertama Melalui Efektivitas Kualitas Sarana dan Prasarana - Nafala Mufti Naimi; Ega Trisna Rahayu (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
This study analyzes student interest and motivation in learning physical education during the Covid-19 pandemic. A descriptive quantitative approach is a method that the researcher uses in this study. The subjects of this research were 25 students of class VII. The results of the first study without being given PTK can be seen as much as 28% with the criteria of strongly agreeing, 32% of agreeing to criteria, 36% of disagreeing criteria, and 4% of strongly disagreeing criteria after which it is continued by being given CAR, the results of this CAR have increased of the students it is known, two students 8% choose strongly disagree, two students 8% decide to disagree, 13 students 52% decide to agree, and eight students 32% choose strongly agree, In conclusion, the use of facilities and infrastructure can foster enthusiasm or motivation to learn children increasing during the pandemic Keywords: Infrastructure, Learning, Learning Motivation Physical Education